Legal Consequences and Liability of Actions by Directors and Commissioners After Term Expiry - Deny Panjaitan; Hulman Panjaitan; Paltiada Saragi (International Journal of Law, Crime and Justice, 2025)
This study examines the legal consequences and liability arising from actions taken by the Board of Directors and the Board of Commissioners of a limited liability company (Perseroan Terbatas PT) after their official terms of office have expired. Employing a cross-sectional quantitative survey design, a Likert-scale questionnaire was distributed to 270 respondent comprising corporate managers of publicly listed companies on the Indonesia Stock Exchange (large-, mid-, and small-cap) and corporate law practitioners in Greater Jakarta. Construct validity (KMO = 0.68; Bartlett’s Test p < 0.001) and reliability (Cronbach’s α = 0.78–0.84) confirmed the adequacy of the instrument. Descriptive analysis showed moderate mean scores for legal status of actions (Mean = 3.12) and reappointment mechanisms (Mean = 2.75). Pearson’s correlation revealed a significant positive relationship between “ultra vires” actions and civil liability risk (r = 0.582; p < 0.001) as well as criminal liability risk (r = 0.314; p < 0.001), whereas reappointment via the General Meeting of Shareholders (RUPS) correlated negatively with civil (r = –0.423; p < 0.001) and criminal (r = –0.287; p < 0.001) risks. Multiple linear regression reinforced these findings (R² = 0.52 for civil risk; R² = 0.31 for criminal risk). ANOVA indicated that small-cap firms faced the highest civil risk and that practitioners with over ten years of experience reported the lowest concern for criminal risk. These results underscore the need for proactive RUPS scheduling, multi-layered authorization systems, and strengthened compliance functions to mitigate ultra vires risks and reinforce good corporate governance.